2009
DOI: 10.1007/s10493-008-9235-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the new repellent BioUD® against three species of ixodid ticks

Abstract: BioUD with the active ingredient 2-undecanone originally derived from wild tomato plants is a new repellent recently registered by the US EPA. Repellent efficacy of BioUD (7.75% 2-undecanone) and DEET (98.11%) was examined in the laboratory using a choice test between repellent-treated and control filter paper surfaces for Amblyomma americanum, Dermacentor variabilis, and Ixodes scapularis. BioUD provided greater repellency against A. americanum and I. scapularis than DEET. No difference was found between BioU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 30 publications
2
51
0
Order By: Relevance
“…Previously we found that BioUD provided significantly greater mean percentage repellency than 98.1% DEET against A. americanum and equivalent repellency to 98.1% DEET against D. variabilis on treated filter paper compared with untreated controls. 19 Similar results were found in this study when comparing BioUD to 98.1% DEET against D. variabilis, but mean percentage repellency did not differ between BioUD and DEET for A. americanum . Additionally, whereas BioUD was more repellent than DEET for both species in head-to-head trials on filter paper, 19 no difference was found for either species in head-to-head trials on cotton cloth.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Previously we found that BioUD provided significantly greater mean percentage repellency than 98.1% DEET against A. americanum and equivalent repellency to 98.1% DEET against D. variabilis on treated filter paper compared with untreated controls. 19 Similar results were found in this study when comparing BioUD to 98.1% DEET against D. variabilis, but mean percentage repellency did not differ between BioUD and DEET for A. americanum . Additionally, whereas BioUD was more repellent than DEET for both species in head-to-head trials on filter paper, 19 no difference was found for either species in head-to-head trials on cotton cloth.…”
Section: Discussionsupporting
confidence: 86%
“…19 Similar results were found in this study when comparing BioUD to 98.1% DEET against D. variabilis, but mean percentage repellency did not differ between BioUD and DEET for A. americanum . Additionally, whereas BioUD was more repellent than DEET for both species in head-to-head trials on filter paper, 19 no difference was found for either species in head-to-head trials on cotton cloth. This suggests that DEET may bind better to cotton cloth than to filter paper.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The basis for naturally 'tick-resistant' breeds or species of hosts appears to be related to host immune response (Martinez et al 2006), however, differences in volatile emissions (Weldon and Carroll 2007), if present, provide potential compounds useful for livestock protection. Plant-based compounds evaluated against ticks may provide new active ingredients for protection of human and even livestock (Bissinger et al 2009, Dietrich et al 2006, Feaster et al 2009, Palsson et al 2008.…”
Section: Repellentsmentioning
confidence: 99%
“…With the arrival of alternatives to deet-based products (e. g., picaridin, IR3535) in recent years, there has been a growing interest in discovery of tick repellents from natural sources (e.g. Jaenson et al 2005, Tunón et al 2006, Garboui et al 2007, Carroll et al 2007, Bissinger et a. 2009).…”
mentioning
confidence: 99%